2021
DOI: 10.1007/s10803-021-05004-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of COVID-19-Related Stress and Mental Health Problems Among Parents of Children with Developmental Disorders During the Pandemic

Abstract: COVID-19 not only threatens people’s physical health, but also creates disruption in work and social relationships. Parents may even experience additional strain resulting from childcare responsibilities. A total of 129 parents participated in this study. Parents of children with developmental disorders showed higher levels of parenting stress, depressive symptoms, and anxiety symptoms than did parents of children with typical development. Parenting stress and health worries were positively related to mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…In addition, consistent to findings from previous studies ( Asbury et al, 2020 ; Chan & Fung, 2021 ; Thorell et al, 2021 ), our study showed that children with SEN had poorer mental health in comparison to typically developed children. Children with ID or mental disorders had significantly more emotional and behavioural difficulties and poorer quality of life than children with other disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, consistent to findings from previous studies ( Asbury et al, 2020 ; Chan & Fung, 2021 ; Thorell et al, 2021 ), our study showed that children with SEN had poorer mental health in comparison to typically developed children. Children with ID or mental disorders had significantly more emotional and behavioural difficulties and poorer quality of life than children with other disabilities.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of our study suggest that careful clinical attention should be paid to the mental health of parents of children with developmental disorders [ 51 ]. Continuous efforts have evolved in order to provide clinical support to individuals with developmental needs, including those individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Parental involvement in the schooling of the children for example was shown to be more difficult for parents with learning disabilities (Maguire et al, 2009 ; Tarleton et al, 2005 ), ASD (Morris, 2003 ) and ADHD (Sonuga-Barke et al, 2002 ). Survey studies in parents indicated more worries and mood-changes for parents (Asbury et al, 2021 ), more emotional problems for children (Nonweiler et al, 2020 ) and increased levels of parental stress (Bentenuto et al, 2021 ; Chan & Fung, 2021 ; Soriano-Ferrer et al, 2021 ) during the COVID pandemic, both for parents of children with and without DD compared to regular times, with higher baseline and follow-up levels of parental stress in the DD group. The increase of parental stress during lockdown for children with DD was associated with the decrease in therapy (Bentenuto et al, 2021 ).…”
Section: Opportunity-propensity Predictors For (Online) Learning (During Covid-19)mentioning
confidence: 99%